The attitude of Brazilian federal police officers towards firearms - Borba,Alessandra (2021)
Abstract This research deals with one of the most problematic themes in the Brazilian public security agenda, firearm control. Since the publication of the Statute of the Disarmament in 2003, the Federal Police (FP) has been responsible for controlling firearm possession of the civilian population. Thus, FP officers become central players in firearm control policies in Brazil. In this research, we investigate the attitude of Brazilian FP officers towards firearms and what explains this attitude. We collected data from 800 police officers from different positions working in all regions of the country. The results show that police officers believe that firearm possession is an individual right, but firearms do not protect against crime. The results also show that the officers’ attitude towards firearms is influenced by their position and their experience with firearms. The article presents the study’s implications for management theory and practice.